Effects of controlled doses of Oxyelite Pro on physical performance in rats. Issue 1 (December 2016) - Zovico, Paulo; Curty, Victor; Leal, Marcos; Meira, Eduardo; Dias, Daniel; Rodrigues, Lívia; Meyrelles, Silvana; De Oliveira, Edilamar; Vassallo, Paula; Barauna, Valério
Abstract Background OxyElite Pro (OEP) is a dietary supplement to increase metabolism which contains as key stimulant the ingredient 1, 3-dimethylamylamine (DMAA). Serious adverse effects have been reported after OEP consumption however, these effects are related to poisoning or overdose. To our knowledge, no one studied the effects of OEP at controlled doses. Thus, the aim of this study was to evaluate acute and chronic OEP affects, at controlled doses in Wistar rats, on physical performance, metabolic parameters, liver injury markers and oxidative stress markers and mitochondrial biogenesis in skeletal muscle. Methods Rats were divided in control, 4.3 mg OEP/kg, 12.9 mg OEP/kg and 25.8 mg OEP/kg. All groups were submitted to supplementation with OEP for 4 weeks and the experimental protocols were performed 30 min after the first OEP administration (acute response) and 30 min after the last OEP administration at the end of the forth week (chronic response). Results Running distance and running time increased after acute administration of 12.9 mg OEP/kg (2.6-fold) and 25.8 mg OEP/kg (2.8-fold). Since no effect on the exercise tolerance test was observed at the lower OEP dose (4.3 mg OEP/kg), this group was removed from further analyzes. On other hand, running distance and running time decreased after daily supplementation for 4 weeks also in both groups (64% in 12.9 mg OEP/kg and 72% in 25.8 mg OEP/kg). Chronic supplementation at both 12.9 and 25.8 mg OEP/kg decreased TBARS levels in soleus muscle (36 and 31%) and liver (43 and 25%). AOPP was also decreased by both doses in the liver (39 and 45%). Chronic administration of the highest dose, 25.8 mg OEP/kg, was able to reduce mRNA expression of PGC-1α in soleus muscle (25%). No effect was found in other analyses such as spontaneous physical activity, body weight, food and water intake, hepatic toxicity, cardiac oxidative stress and mitochondrial DNA amount. Conclusion Maximum and not recommended doses of OEP ingested acutely presented stimulating effect on the ability to exercise. However, its daily consumption for 4 weeks showed antioxidant effects in soleus muscle and liver which may have decreased the PGC-1α mRNA expression on soleus muscle and contributed to the impaired performance in the exercise tolerance test.